Synthesis of amberlite XAD-2-ANSA resin for separation, preconcentration and spectrophotometric determination of trace elements in food samples - Mohamed Muthana Taher (Ain Shams University, 2018)
A new chelating sorbent has been synthesized using Amberlite XAD-2 resin functionalized with 1-amino-2-naphthol-4-sulfonic acid (ANSA) through -N=N- group. This sorbent, characterized by infrared (FTIR) spectra and optimized for sorption-desorption of the studied metal ions then, it was used as packing for the column for separation/ preconcentration of cadmium, cobalt, and nickel prior to their determination spectrophotometrically. Metal ions of Cd, Ni, and Co sorbed in the column were eluted one by one with 0.02 M, 0.10 M, and 0.20 M HCl acid respectively. Under the optimal conditions, the proposed procedure enabled the determination of Cd, Co, and Ni with detection limits of 0.98, 0.30 and 2.10 μg L− 1 respectively. The developed procedure was evaluated by the analysis of mixed metal ions Cd, Co and Ni solution contained 0.30, 30, and 1.25 µg respectively, and the percentage recovery was 95.5 - 104%. The procedure was applied to the analysis of food samples (grains of Sorghum bicolor), and the results obtained were compared with that of FAAS (before and after separation/preconcentration).